Portretna galerija Attemsov iz dvorca Dornava in drugi portreti Jožefa Digla - Komić Marn, Renata (Kronika (Ljubljana), 2023)
The contribution brings forth new findings about the Baroque painter Joseph Digl († 1765) and his portraits. The painter’s opus, which has so far comprised seven portraits of the Counts of Attems and four altar paintings, has now been expanded by another six portraits revealing that his clientele also included the Counts of Szapáry. Based on the analysis of his links to his patrons and the newly discovered archival sources, it is possible to more precisely follow the life path of Joseph Digl and to confirm his presence in Ljutomer and Bad Radkersburg. Moreover, his comprehensive opus and the splendid ties that he maintained with his clientele rank him among important Baroque portrait painters in Slovenia.
Keywords: art collections; art partonage; Attems; Baročno slikarstvo; Baroque painting; Digl, Jožef; Mecenstvo; portrait painting; Portretno slikarstvo; Slovenia; Szápáry; Umetnostne zbirke